(3RgQI GdWQa hRgQI GdXQa aj HSW GdLed ef GdYQhV Gdegeds - (3CHh HcQ eMeO Hf eMeO Hf EOQjS Hf eGdc Hf YHO GdhGMO Hf YHO Gdedc GdZQGfj GdbVGYj GdZddhTjs
(3ChdgG (B:s
(3GdMeO ddg GdPi CfYe Ydi GdEfSGf HGdJMdi HMdHI Cgd GdHjGf hGdJaff ai Yde GddSGf hHYO aEf GdTYQ deG cGf jYfi GdHdGZI s
(3BNQgG (B:s
(3JfJgi HCKfGA GdaUd GdMGOi YTQ Hbhdg (B: (3hdPdc de jcf dMf EdG Cfg EjbGY aEf GdEjbGY ddMSf HefRdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B3 - (3U (B620s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdYQhV hGdbhGais